The Impact of Integrating Technology in Teaching Listening Skill to Kurdish Students at Preparatory Schools - Payam Aziz Muhammad Nawe; Wirya Omar Amin (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The current study attempts to examine the effectiveness of embedding technology, as an essential topic for educators around the world, with teaching listening skill in the secondary phase for Kurdish students as a solution to motivate the teachers and students to focus on this skill. The traditional in-class vs. the technology-based learningusing approach is compared in an attempt to show how innovative approaches are fruitful. For this purpose, the researcher carried out a quasi-experimental study. Thus, a pre-test post-test research design is utilized, and the sample was taken from Mamun Dabakh preparatory public school for girls in Erbil city. The experiment lasted for eight weeks, and 40 students of the grade 10th were divided into two groups, namely the experimental and the control group. The experimental group is taught by using technology, while the control group was taught traditionally which isreading aloud by the teacher in order to find out the practical techniques and strategies used by teachers in teaching listening skill via technology. The data was collected from the students’ pre-test posttest scores and students’ online progress application, the study results obtained from statistical tests after applied to both control and experimental groups, through using SPSS v-25. So, to achieve that the descriptive statistics are used through statistical mean, standard deviation, t-test, and p-values, as well as charts of frequencies distributions and percentages. However, since the comparative analysis also used and the variability of the results reached, the findings are presented according to the study hypotheses. The main finding of this study suggests that using technology-assisted significantly enhance Kurdish EFL students’ listening and that the experimental group outperformed the control group in their listening subskills.